THE ISSUE OF PROSTITUTION IN THE NOVEL "IN THE COMPANY OF THE COURTESAN" BY SARAH DUNANT(A NEW HISTORICISM APPROACH) - Hani Nur Tanzil, - (2009)
Entitled The Issue of Prostitution in the Novel "In the Company of the Courtesan" By Sarah Dunant (A New Historicism Approach), the present paper concerns the textual analysis of social rules found in the novel "In the Company of the Courtesan", a novel authored by Sarah Dunant, in a new historicism framework proposed by Bressler by using social rules classification proposed by Hart. The present study utilizes a case study research method. The analysis is directed to disclose what social rules that compromise prostitution are and how prostitution is compromised in the text. Based on the findings, it is revealed that folkways, customs, religious rules and laws in Italy compromise prostitution. These social rules point out three things. First, there are rules that promote prostitution. Second, there are rules that regulate prostitution. Third, prostitution is perceived as beneficial for Italian society. The analysis also shows that prostitution is compromised by the depiction of the advantages of prostitution and supporting circumstances that promote or support prostitution, i.e. Italian social rules, economic and war situation. In conclusion, the analysis shows that power has an important role in compromising prostitution.